Effects of dietary gluten on body weight and gut microbiota in BALB-C mice using 16 S rRNA-Based analysis - Merve Sayın Dülger; Nihal Zekiye Erdem; Emek Dümen (Scientific Reports)
Abstract Despite the widespread adoption of gluten-free diets for weight management, the relationship between gluten intake and obesity remains unclear because of the limited number of controlled studies available in the literature. Furthermore, there is ongoing debate regarding the impact of gluten-containing diets on the gut microbiota. This study aimed to investigate the effects of gluten consumption on the body weight and intestinal microbiota of mice fed a high-fat diet. Twenty-four Bagg albino laboratory-bred mice (BALB/c) were randomly divided into four groups for oral gavage feeding: standard diet control (SDC), standard diet + 5 mg/day gluten (SD + gluten), high-fat diet control (HFDC), and high-fat diet + 5 mg/day gluten (HFD + gluten). Each subject’s body weight was measured and recorded weekly. For microbiota analysis, fecal samples were collected weekly from the cages after overnight cage changes. The microbiota was analyzed using via the 16 S ribosomal ribonucleic acid (rRNA) method. Compared with the control diet, both gluten consumption and a high fat diet significantly increased weight gain (p < 0.05). No significant difference was observed in the total mesophilic aerobic bacterial count among the groups (p > 0.05). However, the addition of gluten to the diet positively affected Lactobacillus bulgaricus (p < 0.05). Conversely, gluten-containing diets negatively impacted the total coliform bacteria and Escherichia coli counts in the gut (p < 0.05). These findings suggest that gluten, when combined with either a normal diet or a high-fat diet, contributes to weight gain while exerting positive effects on the intestinal microbiota.